Elements for an Ontology of Theatre - André, João Maria (Filosofia, 2021)
In this study I will seek to characterise, first, the being of theatrical beings in the process of their creation (theatrical poíesis), affirmation, presence, and perception, distinguishing between different types of theatrical beings with different ontological densities, such as what can be termed a “poetic-theatrical body” in its ecstatic emergence, its energy, and its quasi-thing status within a relational ontology; the case of theatrical objects understood as “transitional beings”; and the case of theatrical atmospheres, which are also characterised by the absence of a substantial ontological status. An analysis of the chronotopical inscription of all these types of beings allows me to address scenic space as potential space, as well as the complex webs of theatrical time that cause theatrical action to be ephemeral, unrepeatable, and irreproducible, enhancing the ontological leap between the beings of everyday life and theatrical beings, and dissociating them from the traditional concept of a finished work that endures over time.